Bone Marrow Mesenchymal Stem Cell-Derived Exosomes Accelerate Functional Recovery After Spinal Cord Injury by Promoting the Phagocytosis of Macrophages to Clean Myelin Debris - Sheng, Xiaolong; Zhao, Jinyun; Li, Miao; Xu, Yan; Zhou, Yi; Xu, Jiaqi; He, Rundong; Lu, Hongbin; Wu, Tianding; Duan, Chunyue; Cao, Yong; Hu, Jianzhong (Frontiers in Cell and Developmental Biology, 2021)
Macrophage phagocytosis contributes predominantly to processing central nervous system (CNS) debris and further facilitates neurological function restoration after CNS injury. The aims of this study were to evaluate the effect of bone marrow mesenchyml stem cells (BMSCs)-derived exosomes (BMSCs-Exos) on the phagocytic capability of macrophages to clear myelin debris and to investigate the underlying molecular mechanism during the spinal cord injury (SCI) process. This work reveals that monocyte-derived macrophages (MDMs) infiltrating into the spinal cord injury site could efficiently engulf myelin debris and process phagocytic material. However, the phagocytosis ability of macrophages to clear tissue debris is compromised after SCI. The administration of BMSCs-Exos as an approach for SCI treatment could rescue macrophage normal function by improving the phagocytic capability of myelin debris internalization, which is beneficial for SCI repair, as evidenced by better axon regrowth and increased hindlimb locomotor functional recovery in a rodent model. Examination of macrophage treatment with BMSCs-Exos revealed that BMSCs-Exos could promote the capacity of macrophages to phagocytose myelin debris in vitro and could create a regenerative microenvironment for axon regrowth. In addition, we confirmed that BMSCs-Exos treatment resulted in improved phagocytosis of engulfed myelin debris by promoting the expression of macrophage receptor with collagenous structure (MARCO) in macrophages. The inhibition of MARCO with PolyG (a MARCO antagonist) impaired the effect of BMSCs-Exos on the phagocytic capacity of macrophages and resulted in compromised myelin clearance at the lesion site, leading to further tissue damage and impaired functional healing after SCI. In conclusion, these data indicated that targeting the phagocytic ability of macrophages may have therapeutic potential for the improvement in functional healing after SCI. The administration of BMSCs-Exos as a cell-free immune therapy strategy has wide application prospects for SCI treatment.